2017
DOI: 10.1186/s12916-017-0871-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay for giant cell arteritis – a systematic review and meta-analysis

Abstract: BackgroundGiant cell arteritis (GCA), if untreated, can lead to blindness and stroke. The study’s objectives were to (1) determine a new evidence-based benchmark of the extent of diagnostic delay for GCA and (2) examine the role of GCA-specific characteristics on diagnostic delay.MethodsMedical literature databases were searched from inception to November 2015. Articles were included if reporting a time-period of diagnostic delay between onset of GCA symptoms and diagnosis. Two reviewers assessed the quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 44 publications
5
65
0
2
Order By: Relevance
“…The mean diagnostic delay for those with cranial symptoms is 9 weeks and 17.6 weeks for patients presenting without cranial symptoms, due to a combination of multiple factors including delayed presentation, delayed clinical suspicion and delayed referral for specialist assessment and confirmatory diagnostic tests [68]. Public awareness of GCA is low and primary care doctors are faced with the often nonspecific nature of many early symptoms of GCA and a high prevalence of similar symptoms in the general consulting population [68]. If GCs are started, but specialist referral is delayed, then the potential for a secure diagnosis is reduced, the clinical signs may have resolved and the diagnostic tests are less likely to be positive with increasing time.…”
Section: Fast Track Pathwaysmentioning
confidence: 99%
“…The mean diagnostic delay for those with cranial symptoms is 9 weeks and 17.6 weeks for patients presenting without cranial symptoms, due to a combination of multiple factors including delayed presentation, delayed clinical suspicion and delayed referral for specialist assessment and confirmatory diagnostic tests [68]. Public awareness of GCA is low and primary care doctors are faced with the often nonspecific nature of many early symptoms of GCA and a high prevalence of similar symptoms in the general consulting population [68]. If GCs are started, but specialist referral is delayed, then the potential for a secure diagnosis is reduced, the clinical signs may have resolved and the diagnostic tests are less likely to be positive with increasing time.…”
Section: Fast Track Pathwaysmentioning
confidence: 99%
“…The mean diagnostic delay for those with cranial symptoms is 9 weeks and for those presenting without cranial symptoms is over 17 weeks. There are many factors leading to delay, including delayed presentation, low clinical suspicion, belated referral for specialist assessment, and lack of access to confirmatory diagnostic tests [15]. General public awareness of GCA is low and the early symptoms of GCA are non-specific.…”
Section: Recommendationmentioning
confidence: 99%
“…Clinically it can be difficult to diagnose, because the symptoms can be insidious [15,16]. Evidence suggests that increasing numbers of patients are being investigated for suspected GCA [17].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing GCA early is crucial to prevent irreversible vision loss . Therefore, a recent systematic review, which revealed a mean delay to diagnosis of 9 weeks in patients with GCA (7.7 weeks when patients had a cranial manifestations and 17.7 weeks with non‐cranial manifestations), is a matter of concern. There remains a need to improve strategies for early diagnosis of GCA.…”
Section: Giant Cell Arteritismentioning
confidence: 99%